Attractants for Rhagoletis Batava Obseuriosa, a Fruit Fly Pest of Sea Buckthorn. Issue 4 (2nd October 2019) - Zhao, Bin; Cheng, Tai-Ming; Li, Sha-Sha; Su, Zhi; Wei, Jian-Rong
Abstract: Sea buckthorn, Hippophae rhamnoides, is a widely distributed tree that contributes to soil and water conservation. Its fruit, seeds and leaves are also raw materials for many health products. Rhagoletis batava obseuriosa (RBO) is a fruit fly that attacks sea buckthorn berries; outbreaks have recently been reported on some large-berried cultivars of sea buckthorn in northern China. In order to develop tools to monitor and control of RBO, male lures and food-based attractants of other fruit fly species were evaluated with RBO. Results of the first field bioassays showed that ammonium acetate (AA) was a strong attractant for RBO adults. The subsequent results also showed a trend for ammonium bicarbonate (AB) and ammonium carbonate (AC) trapping an higher number of RBO adults than AA. Mixtures of AA and AC were no more attractive than AC used individually. Further research on attract and kill techniques using these ammonium-based compounds is now required.